Seasonal patterns of greenhouse gas emissions from a forest‐to‐bog restored site in northern Scotland: Influence of microtopography and vegetation on carbon dioxide and methane dynamics. (6th November 2020) - Mazzola, Valeria; Perks, Mike P.; Smith, Jo; Yeluripati, Jagadeesh; Xenakis, Georgios
Abstract: Northern peatlands play an important role in the regulation of the atmospheric greenhouse gas (GHG) balance, functioning as a net carbon sink with low rates of organic decomposition. However, perturbations such as drainage increase peat oxidation, which may lead to enhanced gaseous release of carbon. For this reason, the number of restoration projects that aim to rewet blanket bogs has increased in the last few years, but there is still a lack of understanding of the impact of restoration on emissions of greenhouse gases, such as methane, particularly in sites restored from forestry. In this paper, we investigate the seasonal greenhouse gas dynamics in a forest‐to‐bog restoration site in Scotland. We analyse the effects of restoration on both carbon dioxide and methane fluxes, and investigate which site factors (microtopography, vegetation type, soil moisture and temperature) drive the processes of gaseous exchange between the bog surface and the atmosphere. Our results show that the original surface is near greenhouse gase equilibrium at −0.28 gCO2 eq m 2 ·day −1 and that microtopographic features act as a net greenhouse gas sink (ridges = −0.94 gCO2 eq m 2 ·day −1 and furrows = −0.86 gCO2 eq m 2 ·day −1 ), whereas the bog pool is a net source of greenhouse gases (0.98 gCO2 eq m 2 ·day −1 ). We found different vegetation species play a key role in greenhouse gas flux dynamics, especially in forestry‐derived microtopographical features, and their presence and influence on greenhouse gas dynamics should be accounted for to provide a more comprehensive understanding of emissions associated with restoration management practices. Highlights: GHG (CO2 and CH4 ) dynamics in a boreal peatland restored from forestry are mainly affected by microtopography and vegetation. Forestry‐derived microforms (ridges and furrows) are better GHG sinks than pools (GHG emitters) and original surfaces (near GHG equilibrium). The presence of Trichophorum cespitosum leads to higher CH4 emissions. Restoration practices like terraforming may create a short‐term pulse net GHG emission due to an increase of both CH4 and CO2 fluxes.